Studi Fenomenologi Mandatory Sertifikasi Halal Di Papua: Pendekatan Maqasid Syariah Imam Abu Zahrah - Kamaluddin, Imam; Jakiyudin, Ahmad Havid; Roslan, Isma Aulia (Pusat Kajian Halal Undip, 2023)
The halal mandatory forces business actors in Papua to carry out halal certification. So far, business actors in Papua do not know the essence of mandatory halal and its implications. This study aims to examine the mandatory halal phenomenon that applies to business actors in Papua. Imam Abu Zahrah's sharia maqasid approach serves to interpret this phenomenon. A qualitative descriptive research method with a phenomenological study approach was used in this study. Data collection by means of passive participatory observation and exploration of normative juridical literature. The results of the study show that mandatory halal is able to have a positive impact on economic growth and development in Papua. With mandatory halal, business actors in Papua can increase the existence of their products, especially for local products in terms of market expansion. From the perspective of Imam Abu Zahrah's maqashid sharia, the mandatory granting of halal certification fulfills maslahah on three elements. First, tahdzib al fard in the form of providing education to business people in Papua about the importance of halal products for consumers. Second, Iqamah Al'Adalah (upholding justice) in the form of the generalization that all products produced by Muslim or non-Muslim business actors have the right to obtain halal certification. Third, Jalb Al Maslahah (public interest) in the form of rights for consumers throughout Indonesia that the products consumed from Papua are clearly halal for the benefit.